Влияние противоэпилептических препаратов на судорожную активность в условиях корнеального киндлинга у мышей и модуляции активности ферментов системы цитохрома Р450 - Бойко, Ю. А.; Танцура, Евгений Александрович (Полтавський державний медичний університет, 2019)
Целью работы было изучение фармакодинамики антиэпилептических препаратов в условиях сформированного киндлинг-синдрома при предварительного введения противосудорожных веществ воз действующих на систему цитохрома Р450. Киндлинг-синдром у мышей вызывали путем многократно повторяющейся корнеальной элекстростимуляции при одновременном введении карбамазепина и сультиама. После развития устойчивого генерализованного киндлинг-синдрома проводили исследование противосудорожной активности сультиама, леветирацетама, карбамазепина, вальпроата, ламотриджина и ретигабина. Предварительное введение карбамазепина существенно снижало выраженность его противосудорожной активности при последующем приеме. Введение ламотриджина давало существенный противосудорожный эффект в группе сультиама, в группе карбамазепина достоверное противосудорожное действие отсутствовало. Многократное введение сультиама сопровождалось достоверным противосудорожным эффектом во всех группах, однако наибольшим он был в группе предварительно получавшей сультиам (1,5-1,77 балла). Фармакодинамика вальпроата была схожей с фармакодинамикой сультиама. Предварительное введение карбамазепина, который является индуктором системы цитохрома Р450, приводит к ослаблению противосудорожной активности препаратов метаболизируемых данной ферментной системой (карбамазепин, вальпроат) и формированию фармакологической резистентности к действию указанных препаратов. Также впервые было показано снижение противосудорожной активности ламотриджина в условиях предварительного введения карбамазепина. Сультиам, подавляющий активность системы цитохрома Р450, напротив, увеличивал противосудорожный эффект ламотриджина. Полученные данные имеют важное значение для понимания механизмов взаимодействия антиэпилептических препаратов в условиях комбинированного применения.

Pharmacoresistant epilepsy refers to forms of epilepsy that are poorly therapeutic and its pathogenetic mechanisms are not well understood. The purpose of this work was to study the pharmacodynamics of anti-epileptic drugs in the conditions of the established Kindling syndrome against the background of the prior introduction of anticonvulsant substances acting on the cytochrome P450 system. The work was carried out on white outbred mice-males. Kindling syndrome was caused by repeated corneal electrostimulation. Simultaneously with the formation of Kindling syndrome, intragastric administration of carbamazepine and suliam was performed as an activator and inhibitor of the cytochrome P450 system, respectively. After the development of persistent convulsive syndrome with an intensity of at least 5 points in all animals, the study of the anticonvulsant activity of the following drugs – sultiam, levetiracetam, carbamazepine, valproate, lamotrigine, retigabine – was conducted. Also investigated the behavioral activity of experimental animals in the test «Open field» and «Black and white camera». We have shown that the preliminary administration of carbamazepine for 17 days seriously reduces its anticonvulsant activity upon subsequent administration. Preliminary administration of suliam, on the contrary, increased the anticonvulsant effect of subsequent administration of carbamazepine (2.7-2.8 points). The introduction of lamotrigine gave a significant anticonvulsant effect in the group of stuliam, in the group of carbamazepine a significant anticonvulsant effect was absent. The introduction of stuliam caused a significant anticonvulsant effect in all groups, however, it was the greatest in the group previously treated with slimeam (1.5-1.77 points). The pharmacodynamics of valproate was similar to pharmacodynamic sultiam. For levetiracetam and retigabine, non targeted results were obtained, which are likely to be related to the pharmacokinetics of these drugs. The effect on behavioral activity was provided by stuliam and lamotrigine (a decrease in horizontal and vertical motor activity), as well as retigabine (an increase in research activity). Preliminary administration of carbamazepine, which is an inducer of the cytochrome P450 system, leads to a weakening of the anticonvulsant activity of drugs metabolized by this enzyme system (carbamazepine, valproate) and the formation of pharmacological resistance to the action of these drugs. Also for the first time, a decrease in the anticonvulsant activity of lamotrigine was shown under conditions of prior administration of carbamazepine. Sultiam, which suppresses the activity of the cytochrome P450 system, on the contrary, increased the anticonvulsant effect of lamotrigine. The obtained data are important for understanding the mechanisms of interaction of antiepileptic drugs under combined use.
The effect of antiepileptic drugs on convulsiv activity ander conditions of corneal kindling in mice and modulation of the activity of cytochrome P450 enzymes
Keywords: фармакорезистентная эпилепсия; корнеальный киндлинг; сультиам; карбамазепин; pharmacoresistant epilepsy; corneal kindling; sultiam; carbamazepine